2013
DOI: 10.3344/kjp.2013.26.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Palonosetron, a 5-HT3 Receptor Antagonist, on Mechanical Allodynia in a Rat Model of Postoperative Pain

Abstract: Background5-hydroxytryptamine 3 (5-HT3) receptors have been known to be associated with the modulation of nociceptive transmission. However, it is uncertain whether 5-HT3 plays a role in the antinociceptive or pronociceptive pathway for incisional pain. In this study, we evaluated the effects of palonosetron, a 5-HT3 receptor antagonist, on incisional pain in rats when administered intrathecally or intraplantarly.MethodsAn intrathecal catheter was implanted through the cisterna magna and placed in the intrathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The last possibility among other things may be a reason why headache is one of the most common side effects associated with the use of setrons . The data demonstrating the inefficacy of setrons in experimental pain tests also argue for the proposal above . Furthermore, the dual character of 5‐HT3 receptor‐mediated effects of serotonin on nociception predetermines the possibility of any kind of dose‐dependent response occurring under 5‐HT3 receptor blockade.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The last possibility among other things may be a reason why headache is one of the most common side effects associated with the use of setrons . The data demonstrating the inefficacy of setrons in experimental pain tests also argue for the proposal above . Furthermore, the dual character of 5‐HT3 receptor‐mediated effects of serotonin on nociception predetermines the possibility of any kind of dose‐dependent response occurring under 5‐HT3 receptor blockade.…”
Section: Discussionmentioning
confidence: 57%
“…4 The data demonstrating the inefficacy of setrons in experimental pain tests also argue for the proposal above. 30 Furthermore, the dual character of 5-HT3 receptormediated effects of serotonin on nociception predetermines the possibility of any kind of dose-dependent response occurring under 5-HT3 receptor blockade. The bell-shaped inverted dose-dependent facilitatory effect of granisetron on the ongoing activity of the VPM thalamic neurons, which we revealed in the present study, supports this view; the previous studies also reported similar dose-response curves for effects of setrons.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT 3 receptor is known to have pronociceptive abilities and to relate to the spinobulbospinal loop that is stimulated by superficial neurokinin 1 receptor-expressing neurons [ 24 ], and McClean et al [ 25 ] have reported that ondansetron was effective in alleviating chronic neuropathic pain. To date, there are no published data available regarding the antinociceptive effect of palonosetron other than one study showing that palonosetron had no effect on modulation of mechanical allodynia in a postoperative rat pain model [ 26 ].…”
Section: Discussionmentioning
confidence: 99%